Analysing the contribution of trees and green spaces to household nutrition security in eThekwini, KwaZulu-Natal, South Africa - Bhebhe, Qhelile Ntombikayise; Siwela, Muthulisi; Ojo, Temitope O.; Hlatshwayo, Simphiwe Innocentia; Mabhaudhi, Tafadzwanashe; Slotow, Rob; Ngidi, Mjabuliseni S. C. (Frontiers in Sustainable Food Systems, 2024)
Food from trees and green spaces can diversify diets and enhance food and nutrition security for households. However, sourcing food from these areas often receives little attention in addressing nutrition issues. This study assessed the contribution of trees and green spaces to household food consumption and nutrition in the eThekwini Municipal Area (EMA) located in KwaZulu-Natal South Africa, focusing on the Osindisweni and Maphephetheni communities, which are biologically diverse and face high poverty, unemployment, and food insecurity. Using stratified random sampling, 280 households were selected to complete questionnaires. Additionally, two Focus Group Discussions (FDG's) and key informant interviews were conducted with community members and municipal representatives. Data were analysed using descriptive statistics, the Household Food Consumption Score (FCS), Ordered Logistic Regression and a thematic analysis was done to analyse responses from Focus Group Discussions. The results showed that 93.6% of households consumed acceptable diets, with only 5.0% in the borderline and 1.4% in the poor categories. Specifically, Osindisweni and Maphephetheni households reported 93.3% and 93.7% acceptable diets, respectively. Ordered logistic regression indicated that both cultivated and uncultivated green spaces, household size, number of dependants, as well as access to training, agricultural assistance, extension, and advisory services negatively correlated with nutrition security. While communities recognised the contributions of trees and green spaces, they believed that these sources alone were insufficient. It is concluded that consumption of products from trees and green spaces likely did not improve the nutrition security of the households. To improve household nutrition security in eThekwini, it is vital to foster collaboration among stakeholders, including nutritionists and extension agents. Strengthening the knowledge of extension officers regarding the harvesting and consumption of food from trees and green spaces is crucial for disseminating effective guidance to households, thereby enhancing nutrition outcomes.